Endangerment of YoruÌ€baÌ Individual Names: Implication on YoruÌ€baÌ True Identity - Samuel, Akintoye Oluwole; Adekunle, Ojo George (Journal of Language and Literature, 2020)
Name plays an important role in YoruÌ€baÌ society. YoruÌ€baÌ does not bear names without considering some factors because of its future consequences. Although, name is for identification, it also serves as a source of honour and pride, especially for those who are born from heroic and warrior families. People love identifying with such names by bearing the names of the heroes or warriors. These names have been reduced to surnames today. Other names are praise namely AÌ€moÌ€Ì£keÌÌ£, AÌ€riÌ€npeÌ€, AÌ€moÌ€Ì£oÌ, AlaÌ€niÌ, AÌ€kaÌ€nkeÌÌ£, and AÌ€beÌ€Ì£keÌÌ£. These names are regarded as archaic today and nobody reckon with them anymore. It is dismal that these names and many others that are associated with deities are gradually going into extinction owing to modern religions. This forms the discussion of this paper.Â  The purpose of the paper is to call the attention of YoruÌ€baÌ scholars to the fact that not only YoruÌ€baÌ language is going into extinction, YoruÌ€baÌ original names also do. The data collection for the paper is drawn from texts and journals on YoruÌ€baÌ names. An interviewed was conducted among the youths and the informants who are between 70 and 75 years old from AdoÌ- EÌ€kiÌ€tiÌ€ were consulted. They are selected because aged people value names unlike the youths who bear names without minding the implication. The JAMB admission broad sheet students seeking admission into EÌ€kiÌ€tiÌ€ State University, AdoÌ- EÌ€kiÌ€tiÌ€, Nigeria and the Faculties final admission lists sent to the Faculty of Arts were consulted. The data cover three sessions; 2016/17, 2017/18, 2018/19. This is possible because the researcher is in-charge of admission process in his Department. The paper adopts descriptive approach for the data analysis.